European Union „Better Regulation” Program and its impact on the competitiveness of New Member States - Freyberg, Ewa (Publishing House of the Wrocław University of Economics, 2009)
Almost all reports and studies analyzing the consequences of two last EU enlargements (2004 and 2007) underpin the role of institutional business environment and regulation quality as an important factor of New Member States economic development. 10 of 12 New Member States are countries which have transformed their economy from the central planning system into the market economy. They have to change the relations between institutions, the market and civil society to accelerate their growth. Regulatory reform introduced in 1995 by the OECD and continued by EU (2002) helps to achieve this goal by increasing competition through economic liberalization, including privatization and withdrawal from government intervention into market functioning.1 The impact of regulatory reforms on growth is not easy to measure, but there exist some OECD studies showing positive correlation between the regulation quality of product markets and the productivity of capital and labour, mostly in the medium and long term.2 Especially important are the gains of innovation achieved through market-opening, increased flexibility in the labour market and the creation of new job opportunities. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 154-163